PECULIARITIES OF A TOPICAL TREATMENT OF INFLAMMATORY DISEASES OF ENT-ORGANS IN CHILDREN - S.A. Ivanichkin ("Paediatrician" Publishers LLC, 2011)
Nowadays infectious-inflammatory diseases of ENT-organs take one of the leading positions among pediatric acute pathology including that of infants. Despite abundant information upon etiology and pathogenesis of these diseases there are still questions regarding the most effective therapeutic schemes. This article contains information about peculiarities of pediatric ENT inflammatory diseases treatment. Special attention is paid to the problem of topical treatment of pediatric infectious-inflammatory ENT-diseases. It also includes discussion of benefits and drawbacks of various treatment options and medications used in this field. Key words: pharyngitis, tonsillitis, topical treatment, lozenges. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 72-76.)